Identification of potential VP40 inhibitor of Marburg virus through molecular docking, pharmacokinetic analysis and molecular dynamics simulation - Rohit Das; Anil Bhattarai; Buddhiman Tamang; Nagendra Thakur (Scientific Reports)
Abstract West Africa has been experiencing a resurgence of Marburg virus disease (MVD), a zoonotic pathogen that causes severe hemorrhagic fever in both humans and primates. Regretfully, there are not any effective medications on the market right now. The binding interactions between MARV VP40, a protein essential to viral replication, and a commercial medication, estradiol benzoate, and a natural substance, procyanidin, were examined in this work. Ten hydrogen bonds and hydrophobic interactions with important residues (Ala316, Val317, Lys230, Glu89, Asn87) stabilized procyanidin’s superior binding affinity (− 11.3 kcal/mol) over estradiol benzoate (− 8.9 kcal/mol), according to molecular docking. With a lower radius of gyration (1.94 nm) and RMSD (0.28 nm) than estradiol benzoate (RMSD: 0.37 nm, Rg: 1.97 nm), procyanidin formed a more stable complex, according to molecular dynamics simulations conducted over 200 ns. Additionally, procyanidin showed decreased solvent accessibility and increased intermolecular hydrogen bonding (average 3.50 bonds), suggesting stronger binding. Procyanidin’s superior drug-likeness, decreased cardiotoxicity, and decreased carcinogenicity potential were all shown by ADMET analysis. Its higher binding energy (− 57.82 KJ/mol) was further validated by free energy calculations (MM-PBSA). According to these results, procyanidin, a natural substance shows promise as an antiviral medication against MARV targeting its VP40 protein.